Identification of Histoplasma causing an unexplained disease cluster in Matthews Ridge, Guyana - Ji Wang; Weimin Zhou; Hua Ling; Xiaoping Dong; Yi Zhang; Jiandong Li; Yong Zhang; Jingdong Song; William J. Liu; Yang Li; Ruiqing Zhang; Wei Zhen; et al. (Elsevier, 2019)
Here, we report the identification of Histoplasma causing an unexplained disease cluster in Matthews Ridge, Guyana. In March 2019, 14 employees of Chongqing Bosai Mining Company, China, working in a manganese mining of Guyana, had unexplained fever, and two of them died. We obtained lung and brain tissues as well as the blood samples from the two deceased cases (patient No. 1 and 2), and bronchoscopy lavages and cerebrospinal fluid samples from one severe case (patient No. 3), respectively. All samples were tested by pathological examination, high-throughput sequencing, and real-time PCR. Pathological detection showed the presence of spore-like structures in the lung tissue of patient No. 1, indicating a fungal infection in this patient. Nanopore sequencing identified the existing of H. capsulatum in the lung tissue sample within 13 h. Next-generation sequencing identified specific fragments of H. capsulatum in all of the samples tested (lung, brain and blood serum from the deceased cases, and plasma from the severe case). Real-time PCR assays did not reveal any viral infection related to transmission from bat feces. We conclude that H. capsulatum was the causative pathogen of this disease cluster based on epidemiologic, clinical, pathological and nucleic acid evidence.